Medical professionals' perceptions of the use of treatment rooms. Issue 2 (3rd April 2017) - Diener, Marissa L.; Choi, Chansong S.; Isabella, Russell A.; Lofgren, Abigail Owens; Magana, Sydney
ABSTRACT: Although the use of treatment rooms (as opposed to the child's hospital room) is considered the standard of care for many hospitals in the United States, little research has addressed medical professionals' perceptions of this approach to treatment. This study examined medical professionals' perceptions of the use of treatment rooms for intravenous (IV) procedures with young children. Physicians, nurses, child life specialists, and IV team members at a large, regional, children's hospital completed a survey about their perceptions of the use of treatment rooms for IV insertions. Nurses and IV team members perceived greater administrative challenges and negative impacts and fewer benefits to children with the use of treatment rooms than did child life specialists. Specific concerns and challenges with the use of treatment rooms were identified. Features of an ideal treatment room were also noted. The results of this study provide valuable knowledge on how staff members perceive the use of treatment rooms and suggest greater education and explicit policies on the use of treatment rooms are needed. Furthermore, policies on the use of treatment rooms need to consider the administrative challenges identified, as well as the design features of an ideal treatment room.